Internal Diversity Iranian Germans Between Local Boundaries and Transnational Capital - Moghaddari, Sonja (Global Diversities,, 2020)
This book explores the interrelation between diversity in migrants' internal relations and their experience of inequality in local and global contexts. Taking the case of Hamburg-based Iranians, it traces evaluation processes in ties between professionals - artists and entrepreneurs - since the 1930s, examining migrants' potential to act upon hierarchical structures. Building on long-term ethnographic fieldwork and archival work, the book centers on differentiation, combining a diversity study with a focus on locality, with a transnational migration study, analysing strategies of capital creation and anthropological value theory. The analysis of migrants' agency tackles questions of independence and cooperation in kinship, associations, transnational entrepreneurship and cultural events within the context of the position of Germany and Iran in the global politico-economic landscape. This material will be of interest to scholars and students of anthropology, sociology, migration, urbanism and Iranian studies, as well as Iranian-Germans and those interested in the entanglement of global and local power relations.